Characteristics of ash and particle emissions during bubbling fluidised bed combustion of three types of residual forest biomass - Ribeiro, João Peres (2017)
Combustion of residual forest biomass (RFB) derived from eucalypt (Eucalyptus globulus), pine (Pinus pinaster) and golden wattle (Acacia longifolia) was evaluated in a pilot-scale bubbling fluidised bed reactor (BFBR). During the combustion experiments, monitoring of temperature, pressure and exhaust gas composition has been made. Ash samples were collected at several locations along the furnace and flue gas treatment devices (cyclone and bag filter) after each combustion experiment and were analysed for their unburnt carbon content and chemical composition. Total suspended particles (TSP) in the combustion flue gas were evaluated at the inlet and outlet of cyclone and baghouse filter and further analysed for organic and elemental carbon, carbonates and 57 chemical elements. High particulate matter collection efficiencies in the range of 94-99% were observed for the baghouse, while removal rates of only 1.4-17% were registered for the cyclone. Due to the sand bed, Si was the major element in bottom ashes. Fly ashes, in particular those from eucalypt combustion, were especially rich in CaO, followed by relevant amounts of SiO2, MgO and K2O. Ash characteristics varied among experiments, showing that their inorganic composition strongly depends on both the biomass composition and combustion conditions. Inorganic constituents accounted for TSP mass fractions up to 40 wt%. Elemental carbon, organic matter and carbonates contributed to TSP mass fractions in the ranges 0.58-44%, 0.79-78% and 0.01-1.7%, respectively.